Misconceptions on The Concept of Mediation and Conciliation in The Act on Industrial Relations Disputes Settlement - Zamroni, Mohammad (Faculty of Law, Universitas Sebelas Maret, 2021)
Mediation and conciliation are alternatives with varying characteristics acting as a third-party figure in settling disputes in industrial relations. These alternatives are perceived as the same in Act Number 2 of 2004 on Industrial Relations Disputes Settlement. It leads to conceptual errors and causes mistakes in formulating the mediator and conciliator's authority. Therefore, this study analyzed the concepts of mediation and conciliation as regulated in Act Number 2 of 2004 on Industrial Relations Disputes Settlement. This is a normative legal research carried out with the statutory, conceptual, and comparative law approaches. The result showed that the concept of mediation and conciliation formulated in the Act Number 2 of 2004 on Industrial Relations Disputes Settlement deviates from the basic concepts of the mediator and conciliator to make written recommendations. Conceptually, the mediator and conciliator are facilitators incapable and capable of making written recommendations, respectively